Evaluating the Cause of Death in Obese Individuals: A Ten-Year Medical Autopsy Study - Jad Saab; Steven P. Salvatore (Hindawi Limited, 2015)
Background. Obesity is a growing public health problem associated with increased morbidity and rate of death. Postmortem examination is imperative to determine the cause of death, to detect clinically unsuspected disease entities, and consequently to determine the actual impact of obesity on patient mortality. Methods. A total of 849 adult autopsies were retrospectively reviewed. Obese (BMI ≥ 30 kg/m2) and nonobese patients were separately studied. The primary cause of death in each group was categorized into malignancy, infection, stroke, ischemic and nonischemic heart disease, pulmonary embolism, hemorrhage, and primary nonneoplastic diseases of different organ systems. Results. Of 849 autopsies, 32.3% were obese. The leading causes of death in the obese population were malignancy (31.4%), infection (25.9%), ischemic heart disease (12.8%), and pulmonary embolism (6.2%). Obese individuals were statistically more likely to die from pulmonary embolism and liver disease and less likely to die from neurologic diseases and nonischemic heart disease. Conclusion. Autopsies on obese individuals constitute a third of all adult medical autopsies in our center. Increased death rates in the obese due to pulmonary embolism and liver disease should receive special clinical attention. Autopsy findings in the obese population should contribute to overall premortem disease detection, prevention, and management.